Comparison of Corneal Biomechanical Properties between Post-LASIK Ectasia and Primary Keratoconus. (26th October 2020) - Zhao, Wuxiao; Shen, Yang; Jian, Weijun; Shang, Jianmin; Jhanji, Vishal; Aruma, Aruma; Zhou, Xingtao
Abstract : Purpose . To compare the corneal biomechanical properties between post-LASIK ectasia and primary keratoconus. Methods . A total of 42 eyes of 42 patients with matching age and central corneal thickness (CCT) were divided into two groups according to diagnosis of post-LASIK ectasia (PLE group; n = 21; age range: 22–47 years) and primary keratoconus (KC group; n = 21; age range: 21–47 years). The corneal biomechanical properties were assessed using Scheimpflug-based technology (Corvis ST; Oculus Optikgeräte, Wetzlar, Germany). The paired t -test and linear regression analysis were performed. Results . The PLE group had significantly higher mean stiffness parameter at the first applanation (SP-A1; 76.65 ± 21.66 vs 52.72 ± 13.65, p ≤ 0.001 ) and mean stress-strain index (SSI) (SSI: 0.78 ± 0.16 versus 0.64 ± 0.12, p = 0.001 ) than the KC group. SP-A1 was positively correlated with CCT in the PLE group (Pearson's r = 0.816, p ≤ 0.001 ), but not in the KC group (Pearson's r = −0.014, p = 0.952 ). No statistical correlation was observed between SSI and CCT in either group (Pearson's r = 0.292, p = 0.199, and Pearson's r = 0.004, p = 0.985, respectively). Conclusions . In our case series, KC manifested more severe than PLE in biomechanical properties. Since SSI measurements were independent of corneal thickness, it can be used for corneal biomechanical assessment.